2016
DOI: 10.1037/pst0000052
|View full text |Cite
|
Sign up to set email alerts
|

Psychoanalytic psychotherapy with a client with bulimia nervosa.

Abstract: This case study presents the progress of one patient with bulimia nervosa who was originally very compromised in psychological domains that are the focus of analytic treatment, and includes in-session therapeutic process and a range of outcomes, for example, eating disorder symptoms, attachment status, and reflective functioning. Nested in a study showing more rapid behavioral improvement in subjects receiving cognitive behavior therapy than in subjects receiving psychoanalytic psychotherapy, the case highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…To illustrate the use of CaSE Purpose-based Evaluative Framework for Systematic Case Studies, a case study by Lunn, Daniel, and Poulsen (2016) titled 'Psychoanalytic Psychotherapy With a Client With Bulimia Nervosa' was selected from the Single Case Archive (SCA) and analysed in Table 14. Based on the core questions associated with the six purpose-based systematic case study types in Table 13(1 to 6), the purpose of Lunn et al's (2016) case was identified as critical (testing an existing theoretical suggestion).…”
Section: Case Purposementioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate the use of CaSE Purpose-based Evaluative Framework for Systematic Case Studies, a case study by Lunn, Daniel, and Poulsen (2016) titled 'Psychoanalytic Psychotherapy With a Client With Bulimia Nervosa' was selected from the Single Case Archive (SCA) and analysed in Table 14. Based on the core questions associated with the six purpose-based systematic case study types in Table 13(1 to 6), the purpose of Lunn et al's (2016) case was identified as critical (testing an existing theoretical suggestion).…”
Section: Case Purposementioning
confidence: 99%
“…Furthermore, assessing the case against its purpose will let reviewers determine whether the case achieves its set goals (research objectives and aims). The example below shows that Lunn et al's (2016) case is successful in functioning as a critical case as the authors provide relevant, high-quality information about their tested therapeutic conditions.…”
Section: Case Purposementioning
confidence: 99%
“…By these patients, binging and purging episodes can be experienced as an undisturbed space or a "comfort zone," leading away from these difficult emotional states (Lunn and Poulsen 2012, p. 50). Additionally, bulimic symptoms, which are often triggered by feelings of abandonment and anger, may serve the function of regulating the wish for an object (being close to another person) and the separation from it (Lunn and Poulsen 2012).…”
Section: Psychodynamic Model Of Eating Disorders (Ed)mentioning
confidence: 99%
“…Finally, Tasca and colleagues (2009) tested a model of attachment insecurity and its relationship to eating disorder symptoms. As noted in the paper by Lunn and colleagues (2016) in this special issue, attachment theory is an important conceptual framework for understanding eating disorders partly because of its focus on describing specific interpersonal styles and affect regulation associated with particular attachment insecurities. For example, attachment avoidance is associated with dismissing relationships and down-regulating of emotions, and attachment anxiety is associated with a preoccupation with relationships and up-regulating of emotions (Mikulincer & Shaver, 2007).…”
Section: Interpersonally Based Models Of Eating Disordersmentioning
confidence: 99%
“…The Integrative-Dynamic Therapy case presented by Richards, Shingleton, Goldman, Siegel, and Thompson-Brenner (2016) is a novel sequential combination of cognitive–behavioral therapy followed by dynamic psychotherapy for a young adult with bulimia nervosa that likely reflects what most clinicians do in everyday practice. The Psychoanalytic Psychotherapy case presented by Lunn, Poulsen, and Daniel (2016) of a patient with severe personality pathology demonstrates how treatments for eating disorders sometimes must address complex attachment dysfunction, self-organization, and therapist countertransference in order to provide a useful therapeutic experience. Relationship-focused theories and therapies for eating disorders have come a long way over the past decades, thus providing therapists with a wider range of approaches that can be truly personalized to their clients.…”
mentioning
confidence: 99%